Selenite Induces Cell Cycle Arrest and Apoptosis via Reactive Oxygen Species-Dependent Inhibition of the AKT/mTOR Pathway in Thyroid Cancer - Cheng, Zhen; Yu, Shuang; He, Weiman; Li, Jie; Xu, Tianyi; Xue, Junyu; Shi, Peijie; Chen, Shuwei; Li, Yanbing; Hong, Shubin; Xiao, Haipeng (Frontiers in Oncology, 2021)
Thyroid cancer is the most common endocrine malignancy, and its incidence has increased in the past decades. Selenium has been shown to have therapeutic effects against several tumors. However, its role in thyroid cancer and its underlying molecular mechanism remain to be explored. In the present study, we demonstrated that sodium selenite significantly decreased cell viability and induced G0/G1 cell cycle arrest and apoptosis in thyroid cancer cells in a dose-dependent manner. Transcriptomics revealed that sodium selenite induced intracellular reactive oxygen species (ROS) by promoting oxidative phosphorylation. Increased intracellular ROS levels inhibited the AKT/mTOR signaling pathway and upregulated EIF4EBP3. Intracellular ROS inhibition by N-acetylcysteine (NAC) ameliorated the cellular effects of sodium selenite. The in vitro findings were reproduced in xenograft thyroid tumor models. Our data demonstrated that sodium selenite exhibits strong anticancer effects against thyroid cancer cells, which involved ROS-mediated inhibition of the AKT/mTOR pathway. This suggests that sodium selenite may serve as a therapeutic option for advanced thyroid cancer.